SIMULATION ANALYSIS OF THE DISTRIX PROTOCOL FOR POLITICAL REDISTRICTING - (:unkn) unknown (My University, 2023)
This thesis explores the process of political redistricting, a crucial component of ensuring fair representation in legislative bodies. The study first outlines the background and criteria of redistricting in the United States, emphasizing important criteria such as equal population, racial fairness, contiguity, and political fairness. It then focuses on the Distrix protocol for political redistricting in which two or more players (i.e., political parties) take turns assigning small pieces of territory to districts until no more unassigned territory remains. The Distrix protocol was recently introduced in a board game of the same name. After describing the Distrix protocol, we present the results of numerous simulations experiments that explore various scenarios and outcomes. These experiments show how the number of districts, specific game rules, and distribution of voting power within the starting region affect the likelihood of each player winning the game, average number of turns in a game, and distribution of district sizes at the end of the game. Overall, this thesis is the first rigorous study of the Distrix protocol, and it also highlights the role of innovative game-based procedures and board games in offering potential solutions to the complex problem of political redistricting.